Forecasting changes in sea surface temperature in the Gulf of California, and theirs effects on abundance and distribution of reef species - Ayala-Bocos, Arturo (2015)
The Gulf of California is important because of its high biodiversity and because it is a key area for artisanal fisheries in Mexico. There are current concerns regarding threats to the Gulf, such as global warming, that have caused major changes in marine communities. Consequently, the aim of this study was to estimate the possible impact of increasing ocean temperature on key species.  Potential effects of such increase on reef species are thus estimated in this paper. In order to prepare this estimate, sea surface temperature (SST) was obtained from the NOAA database, and a temperature change trend model was constructed. Biological data was obtained from visual censuses of six regions within the Gulf between 2005 and 2007. A stepwise linear model was used to forecast potential changes in species abundance and distribution. It is estimated that by 2050 average temperature will increase 0.63°C, causing abundance of species of economic value to significantly decrease south of 25° N.  Finally, the response of the 20 most abundant fish species in the Gulf was modeled to estimate changes at community structure level. The simulation shows an imbalance in the function and structure of assemblages. Clearly, increasing sea temperature will bring an imbalance in the composition and the ecological function of the reef systems gradually changing the relative abundances of species. Therefore, the implementation of effective monitoring programs of communities would be an essential tool to detect future effects of global warming.